2019
DOI: 10.1167/iovs.18-25845
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia, Blood Lipid Level, and the Risk of Glaucoma: A Meta-Analysis

Abstract: PURPOSE. Previous studies reported that hyperlipidemia and blood lipid levels were associated with glaucoma, ocular hypertension (OHT), and intraocular pressure (IOP). However, studies aimed at investigating this association have yielded conflicting results. Therefore, to shed light on these inconclusive findings, we performed multiple distinct meta-analyses to clarify the association of hyperlipidemia and blood lipid levels with glaucoma, OHT, and IOP. METHODS. A systematic literature search from Embase, Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
104
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 60 publications
7
104
0
3
Order By: Relevance
“…Previous observational studies have shown contradictory results for relationships between plasma lipid levels and the risk of POAG [28][29][30]. A newly published meta-analysis performed by Wang et al [7] found a signi cant association between plasma lipid levels and the risk of POAG. However, considering these observational studies are limited by potential residual confounding and reverse causality, we should interpret these ndings with caution.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous observational studies have shown contradictory results for relationships between plasma lipid levels and the risk of POAG [28][29][30]. A newly published meta-analysis performed by Wang et al [7] found a signi cant association between plasma lipid levels and the risk of POAG. However, considering these observational studies are limited by potential residual confounding and reverse causality, we should interpret these ndings with caution.…”
Section: Discussionmentioning
confidence: 98%
“…Concerning the relationship between plasma lipids levels and POAG, Wang et al [7] clari ed that hyperlipidemia is signi cantly associated with an increased risk of glaucoma based on pooled responses across 18 epidemiological studies. Wang et al speculated that the possible explanation of this association might be that excess blood lipid levels would increase the episcleral venous pressure and blood viscosity, resulting in a consequent decrease in out ow facility [7,32]. Nevertheless, despite the reasonable biological rationale, the causality for the association between plasma lipid levels and the risk of POAG has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations